Associations between teacher–parent relationships and preschool children’s social behavior problems—the chain mediating roles of work–family conflict and parenting self-efficacy - Liu, Guolei; Jin, Zhen; Zheng, Xinhong; Wang, Zixian; Liu, Weina (Frontiers in Psychology, 2024)
In the Chinese cultural context, the collaborative interaction characteristics among three key entities -families, kindergartens, and communities -and the mechanisms of their correlation with preschool children's social behavior problems have not been fully understood yet. Based on ecological systems Theory and social support theory, this study aimed to examine the correlation between parent-teacher relationships and preschool children's social behavior problems in Chinese kindergartens, as well as the mediating role of parents' work-family conflict and parenting self-efficacy. Structural equation modeling was used to test the research hypotheses based on a questionnaire survey of 1,784 parents of preschool children. The main findings of this study are as follows: (1) Parents' perceived positive parent-teacher relationships are negatively correlated with preschool children's social problems. (2) Parents' work-family conflict and parenting self-efficacy mediate the relationship between parent-teacher relationships and preschool children's social behavior problems; (3) Parents' work-family conflict and parenting self-efficacy play a chain mediating role in the influence of the parent-teacher relationship on preschool children's social behavior problems. Taken together, the results collectively further elucidate the correlation between parent-teacher relationships and preschool children's social behavior problems, while also discussing other relevant factors pertaining to children's social behavior problems. Theoretically, this study expands the understanding of how external environmental resources interact with home and family education. Practically, this research indicates that governments, early childhood education institutions, and workplaces need to strengthen their support for family education of preschool children. The findings contribute to promoting a multi-faceted co-operation aimed at enhancing the quality of early childhood education and fostering the social adaptability and holistic development of preschool children.